2006
DOI: 10.1073/pnas.0600843103
|View full text |Cite|
|
Sign up to set email alerts
|

Leishmaniadisease development depends on the presence of apoptotic promastigotes in the virulent inoculum

Abstract: The obligate intracellular pathogen Leishmania major survives and multiplies in professional phagocytes. The evasion strategy to circumvent killing by host phagocytes and establish a productive infection is poorly understood. Here we report that the virulent inoculum of Leishmania promastigotes contains a high ratio of annexin A5-binding apoptotic parasites. This subpopulation of parasites is characterized by a round body shape, a swollen kinetoplast, nuclear con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
195
2
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(209 citation statements)
references
References 43 publications
6
195
2
6
Order By: Relevance
“…6 Indeed, we have also found that during Leishmania infection, disease development relies on the presence of apoptotic-like promastigotes as infection of mice with only viable Leishmania promastigotes does not result in disease development. 1 In this study employing human primary cells, we could confirm apoptotic-like parasites to be crucial for an enhanced parasite survival. To clarify how the apoptotic-like population secures survival of the viable ones, we analyzed their intracellular fate.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…6 Indeed, we have also found that during Leishmania infection, disease development relies on the presence of apoptotic-like promastigotes as infection of mice with only viable Leishmania promastigotes does not result in disease development. 1 In this study employing human primary cells, we could confirm apoptotic-like parasites to be crucial for an enhanced parasite survival. To clarify how the apoptotic-like population secures survival of the viable ones, we analyzed their intracellular fate.…”
Section: Discussionmentioning
confidence: 69%
“…23 Focusing on the latter one, we could already show that the virulent Leishmania inoculum consists partially of apoptotic-like parasites, through which disease development can occur. 1 In the present study we first characterized the apoptotic population and then determined the fate of apoptoticlike Leishmania parasites in human host macrophages and its significance for T-cell activation. We demonstrated apoptotic-like parasites to activate the macrophages´autophagy machinery, hereby dampening T-cell responses and enhancing parasite survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, death of a sub-population of L. major is crucial for the infection process since injection of live parasite only leads to parasite clearance and to the development of host immunity [4]. This parasite mortality occurs naturally within the gut of infected sand flies and generates apoptotic-like L. amazonensis promastigotes that display phosphatidylserine (PS) at their surface, a lipid found on apoptotic cells, which are recognized by phagocytes [5].…”
Section: During the Establishment Of Infection Within Their Mammalianmentioning
confidence: 99%
“…In contrast, infectivity correlated with the increase of apoptotic cells present in the culture (Pearson r = 0.8433; 95% confidence interval 0.4555-0.9621; p < 0.0025), supporting the importance of altruistic apoptotic cells for macrophage inactivation (van Zandbergen et al 2006, Wanderley et al 2006.…”
mentioning
confidence: 93%